COVD-01. VINBLASTINE MONOTHERAPY INDUCTION FOR LOCALISED CNS GERMINOMA DURING THE COVID-19 PANDEMIC. (4th December 2020) - Moleron, Rafael; Stoneham, Sara; Ajithkumar, Thankamma; Cross, Justin; Nicholson, James; Murray, Matthew
Abstract: INTRODUCTION: Patients with localised CNS-germinoma have excellent survival. More recently, intensive inpatient chemotherapy (carboPEI=carboplatin/etoposide/ifosfamide in Europe) has been effectively employed to reduce radiotherapy fields and/or dose. Current research priorities focus on reducing treatment burden and long-term sequelae. Of note, outpatient-based single-agent carboplatin chemotherapy is associated with excellent outcomes in metastatic testicular seminoma (an identical pathology) [Alifrangis, EJC, 2020]. Recently, successful vinblastine monotherapy was reported in localised CNS-germinoma [Murray, Neurooncol-Adv, 2020]. METHODS: Due to the COVID-19 pandemic, adapted UK guidelines for germ-cell-tumour management were distributed, including potential non-standard treatment options that would reduce hospital visits/admissions. A 30-year-old patient presented with a 32mmx30mmx35mm diameter solid+multi-cystic localised pineal CNS lesion, consistent radiologically with a germ-cell-tumour with prominent teratoma component. Investigation revealed negative AFP/HCG markers and biopsy-proven pure germinoma. After appropriate consent, the patient commenced 12-week induction with weekly vinblastine monotherapy (low-grade-glioma dosing [Lassaletta, JCO, 2016]), with wk6&12 MRI re-assessment prior to definitive radiotherapy. RESULTS: Vinblastine was well-tolerated. After initial 4mg/m2 test-dosing (wk1), standard 6mg/m2 was delivered for wk2, but resulted in asymptomatic neutropenia (nadir 0.3x10^9/l) and missed dosing at wk3. Subsequent doses were 4mg/m2, with no further neutropenia. As expected, MRI showed moderate 40% tumour volume reduction by wk12. Surgical resection of the residual presumed teratoma component was undertaken prior to radiotherapy. CONCLUSION: Patients with CNS-germinoma have excellent outcomes and reduction of treatment-effects remains a priority. The exquisite chemosensitivity of germinoma, excellent results from monotherapy for metastatic testicular disease, and early promise of vinblastine monotherapy lend itself to further exploration for CNS-germinoma.